2005
DOI: 10.1590/s0100-69912005000300008
|View full text |Cite
|
Sign up to set email alerts
|

Estudo retrospectivo dos carcinomas epidermóides das vias aerodigestivas superiores com metástases bilaterais

Abstract: ; Abrão Rapoport, ECBC-SP 1 RESUMO: Objetivo: Estudo retrospectivo das características dos carcinomas epidermóides das vias aerodigestivas superiores relacionadas ao desenvolvimento de metástases cervicais bilaterais. Método: Foram revisados os prontuários de 150 pacientes com carcinoma epidermóide de boca, orofaringe, laringe e hipofaringe submetidos a esvaziamento cervical bilateral entre janeiro de 1979 e dezembro de 1996, dos quais foram selecionados 73 pacientes que apresentavam metástases bilaterais conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Amar et al 16 demonstrated statistically significant results in a study of contralateral cervical recurrence in epidermoid carcinomas of the mouth and larynx, showing that contralateral recurrence is related to the site and size of the primary tumor and the presence and number of ipsilateral lymph node involvement. This paper, however, found no relation between contralateral regional recurrence and the site of the primary tumor or lymph node involvement ipsilateral to the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Amar et al 16 demonstrated statistically significant results in a study of contralateral cervical recurrence in epidermoid carcinomas of the mouth and larynx, showing that contralateral recurrence is related to the site and size of the primary tumor and the presence and number of ipsilateral lymph node involvement. This paper, however, found no relation between contralateral regional recurrence and the site of the primary tumor or lymph node involvement ipsilateral to the primary tumor.…”
Section: Discussionmentioning
confidence: 99%